If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3 + 5x) + -3 = 13 (3 * 2 + 5x * 2) + -3 = 13 (6 + 10x) + -3 = 13 Reorder the terms: 6 + -3 + 10x = 13 Combine like terms: 6 + -3 = 3 3 + 10x = 13 Solving 3 + 10x = 13 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3' to each side of the equation. 3 + -3 + 10x = 13 + -3 Combine like terms: 3 + -3 = 0 0 + 10x = 13 + -3 10x = 13 + -3 Combine like terms: 13 + -3 = 10 10x = 10 Divide each side by '10'. x = 1 Simplifying x = 1
| 10=(225-5x)^1/2 | | 3(2x-4)=26 | | (4a+5)(3a-7)=0 | | y=1.2x-2 | | Y=16xsin(x) | | -6(4x+1)+7+9(x-3)=4 | | 7x+3=5-(7x-2) | | 9x+4(2x-7)=23 | | 28=2(v-8)-8v | | .33p+12=10 | | Y=x/7;(-35,-5) | | 25-(x+8)=9x-3 | | 4(x+1.73)=3x | | 5(4x+3)=25 | | 0.03*1000= | | 33(2x-9)=363 | | -6x+18=77-1(4x+9) | | 2x-9=363 | | 49+49+x=180 | | 6(2x-14)=96 | | 4(8x+10)=104 | | y=x^8 | | 9x+4(2x-7)= | | 2x(3x-9)=54 | | 2-2(8-2x)=0 | | 6(x-9)-17=43 | | AD=y-35 | | CD=2y-10 | | BC=2x-5 | | AB=6x+30 | | y=4ln(x^2+3) | | u/15=-9 |